The effect of interaction between salicylic acid and drought stress on growth and photosynthetic rate of Basella alba and B. rubra (Asian Journal of Agriculture, 2023)
Abstract. Ayuningtias AW, Solichatun, Pangastuti A. 2023. The effect of interaction between salicylic acid and drought stress on growth and photosynthetic rate of Basella alba and B. rubra. Asian J Agric 7: 108-115. Basella alba L and B. rubra L are two species of potential drugs and have very potential to develop because of the secondary metabolic content. The change of climate, which is uncertain and prolongs the dry season, is a problem in the cultivation of these plants. Drought stress affects the aspect in growth and photosynthesis rate. The application of salicylic acid tolerated plants due to drought stress and gave a physiologically different response from both plants. This study aimed to determine the interaction effect of Salicylic Acid (SA) on growth and photosynthesis rate in B. alba and B. rubra. A completely random design was used. Two factors of this study were salicylic acid and drought stress. The dosage of salicylic acid were 0 mM, 2 mM, 4 mM, and 6 mM, and field capacities were set by 100%, 75%, 50%, and 25%. Observed data in this study include plant height, leaf area, photosynthesis rate, stomata conductance, and transpiration rate at B. alba and B. rubra. The result showed in B. alba KL 50% and SA 4 mM (50.1 cm2), in B.rubra KL 25% and SA 4 mM (52.9 cm2 ) were the best treatment in plant high. The highest values of leaf area in B. alba are KL 75% and SA 2mM (91.72 cm2), and in B. rubra, are KL 50% and SA 4 mM (122.67 cm2). The treatment KL 50% and SA 6 mM on B. alba showed the highest result in photosynthesis rate, stomata conductance, and transpiration rate (0.8663 µmol m-2 s-1; 0.9468 µmol m-2 s-1; 0.1890 µmol m-2 s-1), in B. rubra the highest value are KL 75% and SA 6mM (0.9202 µmol m-2 s-1; 0.9468 µmol m-2 s-1; 0,105 µmol m-2 s-1). This study concludes that the interaction between salicylic acid and field capacity significantly affects growth and photosynthesis rate.
Keywords: Basella, drought stress, growth, photosynthesis, salicylic acid